Study of Plants used as Cosmetics in Putalibazar, Syangja - Pokhrel, Simran; Sharma, Sushma (Himalayan Biodiversity, 2023)
In recent days, people from developed countries primarily rely on modern synthesized product for their cosmetic needs, while people from developing/ underdeveloped countries still rely on traditional knowledge and uses locally available plants for their cosmetic needs. As Nepal is an underdeveloped country, most of the people who live in rural areas largely depend upon traditional plants for their cosmetic use. The main objective of this study is to identify and enumerate different plant species used as cosmetics in Putalibazar, Syangja. The data on plants used as cosmetics were collected via participant observation and interview methods. The study revealed that 27 plant species belonging to 18 families were cosmetics. Among them, Curcuma longa L., Aloe vera (L.) Burm.f. and Santalum album L. are the most often utilized plants.